Substitution between temporary parental leave and sickness absence - Malin Persson (Institute for Labour Market Policy Evaluation (IFAU), 2011)
This paper studies interrelations between two benefits in the Swedish social insurance system: the sickness insurance and the temporary parental benefit. The level of compensation differs between the two benefits creating an economic incentive for parents to claim temporary parental benefit when being ill. The substitution between the two benefits is studied using a randomized experiment were parents received information that their use of the temporary parental benefit would be subject to intensified monitoring. Receiving this information decreased utilization of the temporary parental benefit but at the same time led to an increase in short-term sickness absence by 4.9 percent. This corresponds to approximately 43 percent of the decreased use of the temporary parental benefit.
Keywords: J22; H55; H51; H30; I38; 330; Social insurance; social experiment; monitoring; moral hazard; Elternzeit; Gesetzliche Krankenversicherung; Ökonomischer Anreiz; Moral Hazard; Schweden